2020
DOI: 10.1101/2020.03.22.002691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topoisomerase 3B (TOP3B) DNA and RNA Cleavage Complexes and Pathway to Repair TOP3B-linked RNA and DNA Breaks

Abstract: 2 HIGHLIGHTS• Method for in vivo detection of TOP3B cleavage complexes (TOP3Bccs) formed both in DNA and RNA, using a religation defective "self-trapping" R338W TOP3B mutant. • First evidence that TDP2 excises TOPccs produced by a type IA topoisomerase. • TDP2 processes both RNA and DNA TOP3Bccs following their ubiquitylation and proteasomal degradation inside cell. • TRIM41 is the first reported E3 ubiquitin ligase for TOP3Bcc ubiquitylation and proteasomal degradation. SUMMARY (150 words)Genetic inactivation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 103 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…The activity of ExoVII appears to be fine-tuned so that it is primed for DNA adducts at the end of 4-nt overhangs, which correspond to trapped type IIA TOPcc in vivo (8,25). We also found that ExoVII can remove DNA gyrase from trapped TOPcc under conditions where the polypeptide is denatured, similar to previous findings for the eukaryotic TDP1 and TDP2 (36)(37)(38)(39)(40)(41). These observations suggest that the substrate binding site of ExoVII is large enough to accommodate the denatured type IIA topoisomerase polypeptide covalently attached to single-stranded 5′-DNA ends.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The activity of ExoVII appears to be fine-tuned so that it is primed for DNA adducts at the end of 4-nt overhangs, which correspond to trapped type IIA TOPcc in vivo (8,25). We also found that ExoVII can remove DNA gyrase from trapped TOPcc under conditions where the polypeptide is denatured, similar to previous findings for the eukaryotic TDP1 and TDP2 (36)(37)(38)(39)(40)(41). These observations suggest that the substrate binding site of ExoVII is large enough to accommodate the denatured type IIA topoisomerase polypeptide covalently attached to single-stranded 5′-DNA ends.…”
Section: Discussionsupporting
confidence: 88%
“…The eukaryotic TDP enzymes cannot efficiently excise TOPcc unless the TOPcc is first unfolded or digested (10,(36)(37)(38)(39)(40)(41). Hence, we examined whether the tyrosyl nuclease activity of ExoVII is capable of excising native trapped DNA gyrase generated with recombinant DNA gyrase and radiolabeled DNA substrates.…”
Section: Denaturation Of Trapped Dna Gyrase Is Required For Exovii-me...mentioning
confidence: 99%
“…Moreover, the presence of divalent ions cannot compensate for the loss of this arginine residue in G-strand religation, resulting in a dominant lethal cell killing because of the accumulation of topoisomerase I-mediated DNA breaks [ 76 ]. A R338W mutation introduced at the corresponding arginine residue in human topoisomerase IIIβ has been shown to facilitate trapping of the intracellular covalent complex with both DNA and RNA [ 77 ], confirming a similar role for this arginine residue in the cleavage and rejoining of the RNA G-strand.…”
Section: Mechanism Of the G-strand Cleavage And Religationmentioning
confidence: 95%
“…Mutations in TDP2 cause intellectual disability in humans, which is thought to arise from the accumulation of DSBs linked to defective TOP2cc repair [ 59 ]. Interestingly, a self-trapping mutant of another topoisomerase, TOP3B (R338W), was also recently shown to crosslink to 5′ ends of both DNA and RNA [ 60 ]. However, whether endogenous TOP3Bccs arise in cells and the impact of these lesions on DNA or RNA processes are still unknown.…”
Section: Dna-protein Crosslinks: a Diverse Class Of Lesionsmentioning
confidence: 99%